Reconstructing the palaeoecology of a middle Permian alkaline lake using molecular fossils, case study of the Lucaogou Formation in the Junggar Basin, NW China - Ding, Wenjing; Hou, Dujie; Li, Li; Jiang, Lian; Zhang, Ziming; Jiang, Yuhan; George, Simon C. (Organic geochemistry, 2024)
•Palaeoecology during deposition of the Lucaogou Formation was reconstructed.•Type Ⅰ aerobic methanotrophs are indicated by abundant 3β-methylhopanes.•2α-Methylhopanes, 7- and 8-methylheptadecanes indicative of cyanobacteria.•Green algae Chlorophyta were the most likely dominant microalgae.•Some aromatic C40 carotenoids diagnostic for green/purple sulfur bacteria. The lacustrine Lucaogou Formation was deposited during the middle Permian in the Junggar Basin, northwestern China. The depositional environment was an alkaline, brackish to saline lake. The biological diversity of the Lucaogou Formation was reconstructed using biologically informative molecules such as n-alkanes, steranes, and hopanes, and the δ13C composition of organic matter. C30 4α-methyl-24-ethylsterane, C31 lanostane, and abundant C30 − C31 3β-methylhopanes were detected in the organic matter, suggesting the presence of type Ⅰ aerobic methanotrophs including the Methylococcaceae. C30 − C31 2α-methylhopanes and 7- and 8-methylheptadecanes are suggestive of the presence of cyanobacteria. Cyanobacteria and green algae are proposed to have made the dominant contribution to the organic matter. The presence of more 13C-enriched hopanoids in the lower unit compared to the upper unit of the Lucaogou Formation suggest a greater contribution of cyanobacteria to the organic matter in the lower unit. The high abundances of C28 and C29 steranes relative to C27 steranes are likely due to green algae from the Chlorophyta, including the class Chlorophyceae. Dinosteranes that are diagnostic for dinoflagellates were not detected. The low concentrations of C40 isorenieratane, renieratane, β-isorenieratane, renierapurpurane, and β-renierapurpurane that are indicative of photosynthetic green and purple sulfur bacteria indicate a minor contribution from Chlorobiaceae and Chromatiaceae to the organic matter. It is inferred that low to moderate amounts of ciliates grew at or below the relatively unstable chemocline in the lake. The presence of C19-norisopimarane, 8β(H)-labdane, and 4β(H)-19-norisopimarane suggests the presence of coniferous plants growing around the lake, probably including Pinaceae, Araucariaceae, Cupressaceae.